International Advisory Councils: A New Aspect of Internationalization - Altbach, Philip; Mihut, Georgiana; Salmi, Jamil (International Higher Education, 2016)
International advisory councils—committees of external experts that help universities discuss performance and suggest future direction—are increasingly common. This article discusses how these councils are organized, their roles and functions, and the contributions that they make to universities.